Kontribusi Lingkungan Keluarga Terhadap Kemampuan Membaca Al-Qur’an Peserta Didik MTs Sains Al-Gebra Kota Sorong - Nur Fitriani Maharani; Rusyaid Rusyaid; Rosdiana Rosdiana (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to analyze the relationship between the family environment and students’ ability to read the Qur’an. The focus of the study is on the extent to which the family environment contributes to explaining variations in the ability to read the Qur’an within the context of formal education. Methods – This study employs a quantitative approach using a causal-associative research design aimed at analyzing the relationship between the family environment and students’ ability to read the Qur’an. Data analysis was conducted using simple linear regression to determine the magnitude of the independent variable’s contribution to the dependent variable. Data was collected via a questionnaire to measure the family environment variable and an oral test to assess Quran reading ability. Findings – The findings of this study indicate that the sample under investigation the family environment does not have a significant effect on the ability to read the Qur’an. This is evidenced by the p-value of 0.901, which is well above the significance threshold of ? = 0.05. The relationship between the two variables is classified as very weak, with a correlation coefficient of only 0.013 and a coefficient of determination (R-squared) of 0.000, indicating that the family environment’s contribution to the variation in the ability to read the Qur’an is nearly zero.Research Implications – The implications of this study suggest that differences in the ability to read the Qur’an are most likely influenced by factors outside the model used, without implying that any single factor is dominant. The generalizability of these findings is limited to the context of this study.